2019
DOI: 10.1039/c9ob01369e
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of donor–acceptor cyclopropanes and N-sulfonyl 1-azadienes towards the synthesis of spiro-cyclopentane benzofuran derivatives

Abstract: An efficient method for the synthesis of spiro-cyclopentane benzofuran derivatives via a MgI2-catalyzed formal [3 + 2] cycloaddition reaction between donor–acceptor cyclopropanes and N-sulfonyl 1-azadienes in good yield has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“… 10 However, only a few catalytic asymmetric syntheses of spiro-cyclopentanone benzofurans are known. 11 Thus, an efficient route for the preparation of such a motif in enantioselective fashion is highly desirable. We speculated that such a motif can be generated by reacting only the C C of aurone-derived α,β-unsaturated imine.…”
Section: Introductionmentioning
confidence: 99%
“… 10 However, only a few catalytic asymmetric syntheses of spiro-cyclopentanone benzofurans are known. 11 Thus, an efficient route for the preparation of such a motif in enantioselective fashion is highly desirable. We speculated that such a motif can be generated by reacting only the C C of aurone-derived α,β-unsaturated imine.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Banerjee and co-workers reported a different reactivity in the presence of an oxygen atom leading to a (3+2) cycloaddition product, namely the spirocyclopentane benzofuran derivative. 26…”
Section: Synthesis Of Nitrogen Heterocyclesmentioning
confidence: 99%
“…However, there is a paucity of examples demonstrating the formation of seven-membered rings through the utilization of DACs as 1,3-dipoles. The challenge lies in the competitive 1,2-addition with DACs to form (3 + 2) cycloaddition products . The first study on (4 + 3) addition with DACs was reported by Ivanova and co-workers in 2008, which disclosed iso-benzofuran as a cyclic diene participating in the cycloaddition reaction with DACs .…”
Section: Introductionmentioning
confidence: 99%